1999
DOI: 10.1097/00005537-199901000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Glomus Tumors

Abstract: This rate of malignancy should advocate against a watchful, waiting approach. Radiation therapy is not advocated as a primary modality for this type of tumor, as it may lead to recurrence/persistence with either subsequent malignant degeneration and metastases or local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 42 publications
2
73
1
3
Order By: Relevance
“…In 1941, Guild first described "glomic tissue" in temporal bone as a vascular tissue in the dome of the [4]. Catecholamine secreting or "functional" tumours occur in 1%-3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In 1941, Guild first described "glomic tissue" in temporal bone as a vascular tissue in the dome of the [4]. Catecholamine secreting or "functional" tumours occur in 1%-3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical evaluation of SDHB may be used to screen for possible hereditary association as in PGLs of other sites. Distant metastasis may occur in up to 5% of cases and appears more common in hereditary cases [39].…”
Section: Hnpgl Sites Of Involvementmentioning
confidence: 99%
“…1,15 Previous findings have indicated that malignancy is least common (2-4%) for jugulo-tympanic tumors, approximately 6% for carotid body tumors, 1,11 and 16 -19% for vagal tumors. 16,17 Although the majority of paragangliomas are benign (i.e., do not metastasize), the preoperative assessment and surgical plan for this tumor should include evaluation for metastases and a plan that addresses treatment of the primary site and possible metastases. For paragangliomas without clinical evidence of lymphadenopathy, removal of adjacent regional lymph nodes is recommended to identify possible occult metastases that would reclassify the tumor as malignant.…”
mentioning
confidence: 99%